(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article describes the theory of the creation of social institutions, the ontology of the social world from the standpoint of the theory of the social reality of the popular philosopher John Searle. The article gives examples of the formation of social institutions by assigning status functions, the relationship of language and power in the context of social reality and the creation of social facts. The author also describes the formation of an institutional reality by developing collective intentionality, representation and declaration of status functions, providing power and formed with the help of linguistic instruments. Key words: social institution, power, language, status-function, ontology of social reality.